Changes in antipsychotics and other psychotropic drugs during a 30-month lifestyle intervention among outpatients with schizophrenia. (17th November 2017) - Højlund, Mikkel; Elliott, Anja Friis; Madsen, Nikolaj Juul; Viuff, Anne Grethe; Munk-Jørgensen, Povl; Hjorth, Peter
Abstract: Background: Patients with schizophrenia have high risk of early death from diabetes and cardiovascular diseases, partly because of poor lifestyle and partly because of long-lasting exposure to antipsychotic treatment. Aims: To investigate the influence of a lifestyle intervention program on changes in psychotropic medication in a non-selected cohort of patients with schizophrenia. Methods: Observational study of outpatients in the Central Denmark Region during a 30-month lifestyle program. Results: One hundred and thirty-six patients were enrolled and 130 were available for analysis. Median follow-up time was 15.9 months (range 1–31 months). Nineteen patients (15%) were not treated with antipsychotic drugs during the study period. 54% of the 111 patients exposed to antipsychotics were subject to monotherapy at index and at follow-up. The median defined daily dose (DDD) of antipsychotics was 1.33 at index (interquartile range (IQR) 0.67–2.00) and 1.07 at follow-up (IQR 0.40–1.50). 52% of the patients experienced a decrease in DDD during the study period (median change 0.33; IQR 1.00–0.43). There were no significant differences between the patients with decreased, stable or increased DDD with regard to age, sex, follow-up time and time since diagnosis. The number of prescriptions was significantly higher in the patients who decreased their DDD and the proportion of antipsychotic depot formulation was higher in those who increased their DDD. Conclusions: Most patients decreased or stabilized their total dose of antipsychotic medication during the study period. Many patients were subject to antipsychotic polypharmacy. The extent of participation in the lifestyle intervention program did not correlate with the changes in dosing of antipsychotic medication.